Fibroblast growth factor 23–secreting pancreaticobiliary malignancy. Issue 1 (February 2018) - Barta, Valerie; Lalkiya, Neel; Phan, Huy; Miller, Ilene; Sachdeva, Mala
Malignancy-related tumor-induced osteomalacia is a rare but important entity. We report the first case of oncogenic renal phosphate wasting in the setting of a pancreaticobiliary malignancy. Our patient presented with refractory hypophosphatemia. Workup revealed high fibroblast growth factor 23 levels as well as a new pancreaticobiliary mass. All other causes of hypophosphatemia were ruled out. With tumor-induced osteomalacia, an accurate diagnosis and location of the offending tumor is essential for appropriate management and treatment.